1984
DOI: 10.1111/j.1365-2125.1984.tb02403.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between debrisoquine oxidation phenotype and the pharmacokinetics and pharmacodynamics of propranolol.

Abstract: 1 The pharmacokinetics and pharmacodynamics of propranolol (80 mg by mouth) were studied in seven extensive and four poor metabolisers of debrisoquine. 2 Evidence for impairment of the 4'-hydroxylation of propranolol was found in poor metabolisers. However, no significant difference was detected in the oral clearance of unchanged drug between the two groups of debrisoquine oxidation phenotypes. 3 Poor metabolisers of debrisoquine did not experience more intense or more prolonged ,8-adrenoceptor blockade than e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 18 publications
2
21
1
Order By: Relevance
“…The fact that propranolol was shown to be sensitive towards CYP2D6 inhibitors (propafenone and quinidine; studies in Caucasians) is in disagreement with the two genetic studies that reported no influence of CYP2D6 activity on the exposure of propranolol in Caucasians (table 3) [68,69]. Propafenone is additionally an inhibitor of CYP1A2 (table 5), an enzyme also involved in the metabolism of propranolol, and the influence of this inhibitor could be explained by changed CYP1A2 metabolism.…”
Section: Relative Exposure Of Cvds With Cyp2d6 Inhibitorscontrasting
confidence: 41%
See 1 more Smart Citation
“…The fact that propranolol was shown to be sensitive towards CYP2D6 inhibitors (propafenone and quinidine; studies in Caucasians) is in disagreement with the two genetic studies that reported no influence of CYP2D6 activity on the exposure of propranolol in Caucasians (table 3) [68,69]. Propafenone is additionally an inhibitor of CYP1A2 (table 5), an enzyme also involved in the metabolism of propranolol, and the influence of this inhibitor could be explained by changed CYP1A2 metabolism.…”
Section: Relative Exposure Of Cvds With Cyp2d6 Inhibitorscontrasting
confidence: 41%
“…The clinical implications for patients of these findings have not been outlined, but an approximately 50-100% difference in exposure ('dose') must empirically be considered as relevant. For propranolol (ß 1/2 -receptor antagonist), it is surprising that the exposure was reported to be unaffected by CYP2D6 activity in Caucasians (PMs versus EMs) [68,69], whereas a 2-fold higher level was observed in Chinese IMs [70,71]. This might indicate that another eliminating pathway(s) than CYP2D6 (e.g.…”
Section: Cyp2d6 Genetics and Variability In Exposure Of Cvdsmentioning
confidence: 89%
“…Ring hydroxylation to form 4-hydroxypropranolol (4HP) is impaired in poor metabolisers (PM) of debrisoquine (Lennard et al, 1984;Raghuram et al, 1984). In this phenotype, P4501ID6 is absent as a result of splicing errors during transcription of the gene (Gonzalez et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro [2] and in vivo studies [3] have suggested that aromatic ring 4-hydroxylation of the drug cosegregates with debrisoquine 4-hydroxylase (CYP2D6) activity, which exhibits a major genetic polymorphism in various ethnic groups [4,5]. The side-chain oxidation of propranolol has been suggested to cosegregate with S-mephenytoin 4'-hydroxylase (CYP2C19) activity [6] which also exhibits a marked genetic polymorphism [7].…”
Section: Introductionmentioning
confidence: 99%